A retrospective analysis of factors associated with difficult endotracheal tube passage with use of the hyper-angled GlideScope blade. Issue 2 (May 2019) - Schechtman, Samuel A.; Mathis, Michael; Muller, Geoffrey; Thompson, Aleda; Shanks, Amy; Stam, Benjamin; Hart, William K.; Tremper, Kevin K.; Healy, David W.
Abstract : Introduction: Videolaryngoscopy is a valuable tool for tracheal intubation. Some videolaryngoscopes such as the GlideScope, use a hyper-angled blade to improve the glottic view. Despite improved visualization, difficulty during GlideScope laryngoscopy may occur during manipulation of the endotracheal tube (ETT). This investigation seeks to identify characteristics and procedural factors associated with difficult or failed ETT passage. Methods: A single institution retrospective cohort analysis was performed for adult GlideScope intubations utilizing a hyper-angled blade. Tube passage was recorded as easy (T1), difficult (T2), or failed (T3). The primary outcome was difficult or failed ETT passage. A nonparsimonious logistic regression model was developed to determine independent predictors of this outcome, with an exploratory analysis conducted by bootstrapping the data across 1000 samples. Subgroup analysis was performed for head and neck surgical cases. Results: A total of 6109 patients met inclusion criteria. In all, 5412 (88.6%) had easy ETT passage, 666 (10.9%) difficult, and 31 (0.5%) failed. Limited view (grades 2a, 2b, 3, and 4) and short thyromental distance (<6 cm) were independent predictors of difficulty or failure. The absence of teeth and use of standard oral ETT sizes 6–8 were negative predictors (protective) for difficulty or failure. In the subgroup analysis, use of laser-safe ETTs also independently predicted difficulty or failure. Conclusions: A relatively high incidence of difficulty during tracheal tube passage using GlideScope hyper-angled blades was observed. Limited videolaryngoscopic view, short thyromental distance, and use of nonstandard ETTs were independent predictors of procedural difficulty.